PEMBERDAYAAN MASYARAKAT DESA SEMBALUN TIMBA GADING KABUPATEN LOMBOK TIMUR DALAM MEWUJUDKAN MASYARAKAT TANGGUH BENCANA - Hariyadi, Hariyadi; Harun, Anandita Cika Maharani; Andi, Affan Pangurangi; Septiana, Ayu; Putri, Lala Rianti Laela; Maulana, Muhamad Arip; Siddiqirly, â Muhammad; Wulandari, Ni Putu Ayu Siva; Nurmanita, Novia; Hidayah, Nurul (Jurnal Wicara, 2024)
The village of Sembalun Timba Gading is part of the 6 village and sub-districts located in the Sembalun district of East Lombok Regency, Nusa Tenggara Barat province. This village is situated at an altitude of 1200 meters above sea level. Timba Gading Villages was previously a part of Sembalun Lawang Village. However, after the regency of East Lombok conducted village expansion in 2011, Timba Gading village became independent as it met the requirements and qualifications as a village based on the population and land area of the village. Timba Gading village has a hilly geographical condition, and field surveys indicate that the village is prone to landslides and floods. This village is identified as a landslide-prone area but lacks evacuation route signs. The Destana program will be implemented to assist the community of Sembalun Timba Gading village in facing disasters. The KKN-PMD UNRAM team will focus on maintaining evacuation route signs at disaster-prone in the village. Additionally, the flagship program includes creating information boards as a precautionary measure against natural disasters. Collaboration with the local Disaster Management Agency (BPBD) wil be conducted to socialize community preparedness for disasters. The team will also conduct socialization on tree maintenance in landslide-prone areas, especially in Sembalun Timba Gading village. Furthermore, there will be a socialization of the mapping results of landslide and flood-prone areas in Sembalun Timba Gading village.